Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae) - Lindsay, Kate G.; Klymko, John; Marshall, Stephen A. (Zootaxa, 2019)
The five Central American and Mexican species belonging to the Curtonotum murinum species complex are described as Curtonotum abrelatas Lindsay sp. nov., C. irksum Lindsay sp. nov., C. notatum Lindsay sp. nov., C. prolixum Lindsay sp. nov. and C. transitus Lindsay sp. nov. Photographic images, a distribution map of species and an identification key are provided.